2021
DOI: 10.3389/fendo.2020.623792
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Function Abnormalities in COVID-19 Patients

Abstract: PurposeThe novel coronavirus COVID-19, has caused a worldwide pandemic, impairing several human organs and systems. Whether COVID-19 affects human thyroid function remains unknown.MethodsEighty-four hospitalized COVID-19 patients in the First Affiliated Hospital, Zhejiang University School of Medicine (Hangzhou, China) were retrospectively enrolled in this study, among which 22 cases had complete records of thyroid hormones. In addition, 91 other patients with pneumonia and 807 healthy subjects were included a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 19 publications
5
63
0
4
Order By: Relevance
“…It was further reported that decreases in T3 levels were more pronounced in the COVID-19 patients than in other critically ill patients. Lower TSH and total T3 levels in COVID-19 patients compared to patients hospitalized for non-COVID-19 pneumonia were also reported in two other studies (49,51). Decreases in total T3 and TSH levels were correlated to increases in pro-inflammatory cytokines, such as interleukin (IL)-2, IL-6, IL-7, interferon (INF)-g, and tumor necrosis factor (TNF)-a. T3 predicted all-cause mortality and IL-6 and C-reactive protein (CRP) were negatively correlated with fT3 levels.…”
Section: Influence Of Covid-19 On Th Levelssupporting
confidence: 54%
See 1 more Smart Citation
“…It was further reported that decreases in T3 levels were more pronounced in the COVID-19 patients than in other critically ill patients. Lower TSH and total T3 levels in COVID-19 patients compared to patients hospitalized for non-COVID-19 pneumonia were also reported in two other studies (49,51). Decreases in total T3 and TSH levels were correlated to increases in pro-inflammatory cytokines, such as interleukin (IL)-2, IL-6, IL-7, interferon (INF)-g, and tumor necrosis factor (TNF)-a. T3 predicted all-cause mortality and IL-6 and C-reactive protein (CRP) were negatively correlated with fT3 levels.…”
Section: Influence Of Covid-19 On Th Levelssupporting
confidence: 54%
“…This theory is supported by the observation that number and intensity of the staining with anti-TSH antibody was decreased in pituitary glands of deceased COVID-19 patients. Decreased TSH levels may result from direct virus attack on TSH-producing cells in the pituitary gland or by action of cytokines (49).…”
Section: Influence Of Covid-19 On Th Levelsmentioning
confidence: 99%
“…Cytokine storm syndrome-a term used to describe the detrimental effects of hypercytokinemia on human cells-has been well described in the literature as the cause of thyroid problems [30]. While it is well documented that this storm is the cause of nonthyroidal illness syndrome seen in COVID-19 patients, at present there is little evidence to suggest the direct thyroid cytotoxic effect of cytokines, at least in humans [30,31]. Immunemediated post-viral inflammatory reaction, involving both the adaptive and innate immune systems, has also been described in the literature as a cause of thyroid problems [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have analyzed the thyroid function in COVID-19 patients and found patterns suggestive of NTIS [14][15][16]20], but very few have reported an association with markers of in ammation. Lui et al found that higher CRP level was independently associated with low FT3.…”
Section: Discussionmentioning
confidence: 99%